Ballad of the Green Beret : the life and wars of Staff Sergeant Barry Sadler from the Vietnam War and pop stardom to murder and an unsolved, violent death /: the life and wars of Staff Sergeant Barry Sadler from the Vietnam War and pop stardom to murder and an unsolved, violent death. (2017) - Leepson, Marc, 1945-
No abstract available